Implementation and application of automata : 24th International Conference, CIAA 2019, Košice, Slovakia, July 22-25, 2019, Proceedings /: 24th International Conference, CIAA 2019, Košice, Slovakia, July 22-25, 2019, Proceedings. ([2019]) - Unknown
No abstract available